Corticofugal and Brainstem Functions Associated With Medial Olivocochlear Cholinergic Transmission - Munoz, Felipe; Vicencio-Jimenez, Sergio; Jorratt, Pascal; Delano, Paul H.; Terreros, Gonzalo (Frontiers in Neuroscience, 2022)
Cholinergic transmission is essential for survival and reproduction, as it is involved in several physiological responses. In the auditory system, both ascending and descending auditory pathways are modulated by cholinergic transmission, affecting the perception of sounds. The auditory efferent system is a neuronal network comprised of several feedback loops, including corticofugal and brainstem pathways to the cochlear receptor. The auditory efferent system’s -final and mandatory synapses that connect the brain with the cochlear receptor- involve medial olivocochlear neurons and outer hair cells. A unique cholinergic transmission mediates these synapses through α9/α10 nicotinic receptors. To study this receptor, it was generated a strain of mice carrying a null mutation of the Chrna9 gene (α9-KO mice), lacking cholinergic transmission between medial olivocochlear neurons and outer hair cells, providing a unique opportunity to study the role of medial olivocochlear cholinergic transmission in auditory and cognitive functions. In this article, we review behavioral and physiological studies carried out to research auditory efferent function in the context of audition, cognition, and hearing impairments. Auditory studies have shown that hearing thresholds in the α9-KO mice are normal, while more complex auditory functions, such as frequency selectivity and sound localization, are altered. The corticofugal pathways have been studied in α9-KO mice using behavioral tasks, evidencing a reduced capacity to suppress auditory distractors during visual selective attention. Finally, we discuss the evolutionary role of the auditory efferent system detecting vocalizations in noise and its role in auditory disorders, such as the prevention of age-related hearing loss.